25 Jahre Galerie Heike Curtze : ein weg. - Curtze, Heike; Galerie Heike Curtze, Wien; Galerie Heike Curtze, Düsseldorf (Wien : Galerie Heike Curtze, 1999)
Attersee, Christian Ludwig ; Babetto, Giampaolo ; Bernsteiner, Georg ; Birkas, Akos ; Blank, Michael ; Borbas, Klára ; Brus, Günter ; Cibulka, Heinz ; Fessler, Winfried ; Grabmayr, Franz ; Kocherscheidt, Kurt ; Leitner-Gründberg, Rudolf ; Messensee, Jürgen ; Nitsch, Hermann ; Ozeri, Yigal ; Peyrer, Uta ; Pfanner, Elisabeth ; Pinter, Klaus ; Prantl, Karl ; Rainer, Arnulf ; Romberg ; Osvaldo ; Schaberl, Robert ; Steiger, Dominik ; Venezia, Michael ; Wallach, Paul ; Werkner, Turi
Duits & Engels
boek